Assessing local perspectives in a forested landscape of central Cameroon - Sassen, M.; Jum, C.N. (2007)
Decision makers require better understanding of local people’s needs in tropical forested landscapes to enable more locally relevant and sustainable conservation. The Center for International Forestry Research (CIFOR) developed a series of survey methods that assess the perceptions and priorities of forest dependent people with regard to their environment. These methods were applied in a fragmented forest landscape in Central Cameroon, near a small forest reserve. The results show that despite the importance of agriculture for food and income, people still rely on the forest for most aspects of their livelihoods. However, people’s relationships with the forest are changing, potentially leading to increased conflicts and resource degradation. These issues are not easily captured in sociological surveys, but the methods applied generated insights into people’s views and preferences regarding the forest and provide grounds for negotiation and compromise between the stakeholders. Future work will link people’s preferences to the results of a biodiversity survey.